Social Media Influence on Investment Decisions: Insights from Nepal's Capital Market - Joshi, Padam Raj; Rawat, Babu Ram (KMC Journal, 2025)
This study investigates the influence of social media and online community groups on individual investors’ decision-making processes, with capital market literacy serving as a mediating factor. The research employed a descriptive and causal-comparative design, utilizing a purposive sampling method to select 384 respondents. Data collection was conducted through a structured questionnaire comprising multiple-choice and Likert-scale items. The reliability of the instrument was evaluated using Cronbach’s alpha, and data analysis was performed using descriptive and regression techniques. The findings indicate that Facebook is the predominant platform utilized by investors, who are primarily between 26 and 35 years of age, hold bachelor’s degrees, and self-identify as having intermediate investment experience. The analysis reveals a statistically significant positive correlation between social media, online community groups, and investment decisions, with capital market literacy partially mediating this relationship. These results underscore the increasing impact of online platforms on investment behaviour and emphasize the necessity for enhancing capital market literacy. Future research should explore the long-term effects of social media on investment performance and examine the influence of various social media types on different investment strategies across demographic groups.